Effectiveness of non-medical health worker-led counselling on psychological distress: a randomized controlled trial in rural Nepal. (2019) - Markkula, N.; Lehti, V.; Adhikari, P.; Peña, S.; Heliste, J.; Mikkonen, E.; Rautanen, M.; Salama, E.; Guragain, B.
Abstract : Background: An essential strategy to increase coverage of psychosocial treatments globally is task shifting to non-medical counsellors, but evidence on its effectiveness is still scarce. This study evaluates the effectiveness of lay psychosocial counselling among persons with psychological distress in a primary health care setting in rural Nepal. Methods: A parallel randomized controlled trial in Dang, rural Nepal (NCT03544450). Persons aged 16 and older attending primary care and with a General Health Questionnaire (GHQ-12) score of 6 or more were randomized (1:1) to receive either non-medical psychosocial counselling (PSY) or enhanced usual care (EUC). PSY was provided by lay persons with a 6-month training and consisted of 5-weekly counselling sessions of 35–60 min with a culturally adapted solution-focused approach. EUC was provided by trained primary health workers. Participants were followed up at 1 (T1) and 6 months (T2). The primary outcome, response to treatment, was the reduction of minimum 50% in the Beck Depression Inventory (BDI) score. Results: A total of 141 participants, predominantly socially disadvantaged women, were randomized to receive PSY and 146 to EUC. In the PSY, 123 participants and 134 in the EUC were analysed. In PSY, 101 participants (81.4%) had a response compared with 57 participants (42.5%) in EUC [percentage difference 39.4% (95% CI 28.4–50.4)]. The difference in BDI scores at T2 between PSY and EUC was −7.43 (95% CI −9.71 to −5.14). Conclusions: Non-medical (lay) psychosocial counselling appears effective in reducing depressive symptoms, and its inclusion in mental health care should be considered in low-resource settings.